Lawan Campak Tanpa Panik: Edukasi Health Talk dan Pemberdayaan Orang Tua di Poli Anak RSUD Cibabat - Sri Hartati; Ratna Wulan Hardian N; Susi Indriani; Alya Raina Alfanaz; Nazlatunnisa; Shelvi Safira; Dina Nur Fauziah; Dion Pilipus (Fakultas Ekonomi dan Bisnis Unversitas Islam Raden Rahmat, 2026)
Measles is a highly contagious acute infectious disease caused by the measles virus (Measles virus) of the genus Morbillivirus in the family Paramyxoviridae. This disease remains a major cause of morbidity and mortality in children, especially in countries with low immunization coverage. The measles virus spreads through respiratory droplets when an infected person coughs, sneezes, or talks, and can even survive in the air and on surfaces for up to two hours. The WHO states that approximately 90% of people without immunity will be infected through close contact with an infected person. The incubation period for measles generally lasts 7–14 days, and an infected person can transmit the virus from four days before the rash appears until four days after the rash appears. This community service activity aims to optimize parental knowledge about managing measles in children through health education. The method used was health education with a pre-post test design on 25 parents of children. Evaluation results showed an increase in knowledge scores after the education. This knowledge optimization is expected to improve families' ability to manage measles independently and safely. Nurses play a strategic role as educators in this community service activity